Comment - Jackson, Moana (Victoria University of Wellington Law Review, 1995)
Moana Jackson provides a brief comment about Māori fisheries and rights at the "Treaty Claims: The Unfinished Business" Conference as part of this special issue of the Victoria University of Wellington Law Review. He argues that there has been a tendency to drown the Treaty of Waitangi in the rhetoric of the law, having been emasculated of its political underpinnings. Jackson notes that the rights bestowed by the Treaty are meaningless without the political authority, whether it is recognised as self-determination or sovereignty. The author concludes that the Treaty is not an illusion of political authority, but rather a reaffirmation of the rights of Māori to determine their own lives.